Effect of Xenon on Proinflammatory Activation and Apoptosis of Human Neutrophils Under Ex Vivo Conditions - O. A. Grebenchikov; A. K. Shabanov; L. L. Nikolayev; A. I. Shpichko; I. V. Bratishchev; L. Yu. Marchenko; Sh. Zh. Khusainov; R. A. Cherpakov; N. P. Shpichko (Неотложная медицинская помощь, 2021)
Background. The syndrome of systemic inflammatory response, which underlies the damaging effect of factors of infectious and non-infectious genesis, may cause multiple organ failure. The degree of its severity is determined, among other things, by the activation of neutrophils. The paper highlights new mechanisms of the anti-inflammatory action of the inhalation anesthetic xenon, mediated by a decrease in the ability of neutrophils to pro-inflammatory response.Aim of study. To evaluate the effect of xenon on the activation of human neutrophils under ex vivo conditions.Material AND methods. We studied the effect of xenon inhalation on reduction of the ability of neutrophils to be activated proinflammatory by reduced expression of adhesion molecules CD11b and CD66b on the surface of neutrophils and on the phosphorylation of proinflammatory kinases: ERK 1/2 and kinase — p38 in neutrophils of healthy volunteers.Results. The use of xenon at a dose of 30 vol. % within 60 minutes in healthy volunteers statistically significantly reduces the ability of neutrophils to proinflammatory activation. The addition of lipopolysaccharide (LPS) to the incubation medium of neutrophils causes their pronounced activation, statistically significantly increasing the phosphorylation of key proinflammatory neutrophil kinases ERK1/2 and kinase p38. Inhalation of xenon in volunteers (30% within 60 minutes) has a pronounced anti-inflammatory effect on LPS-stimulated neutrophils, decreasing their activation by inhibiting pro-inflammatory kinase ERK1/2 and pro-inflammatory MAP kinase p38.Conclusion. The actual study, performed on isolated neutrophils from volunteers who underwent xenon inhalation, revealed the anti-inflammatory properties of the inert gas xenon, which, in our opinion, may have a direct relationship to the identification of the mechanism of its neuroprotective properties. Thus, the research results available today suggest that xenon has a pronounced pleiotropic mechanism of brain protection. This is a partial blockade of NMDA receptors, and phosphorylation of the enzyme glycogen synthase-3β, and limitation of the inflammatory activation of neutrophils.Findings. Inhalation of xenon in volunteers (30% within 60 minutes) has a pronounced anti-inflammatory effect on neutrophils stimulated by lipopolysaccharides, decreasing their activation by inhibiting proinflammatory ERK 1/2 kinase and proinflammatory MAP kinase p38, as well as reducing the expression of markers of activation and degranulation CD11b and CD66b on the surface of neutrophils. Stimulation by lipopolysaccharides statistically significantly reduces spontaneous apoptosis of neutrophils, while xenon increases the ability of neutrophils to apoptosis, which is likely to contribute to the resolution of inflammation.